Membangun kecakapan kewarganegaraan digital melalui implementasi PKn di era revolusi industri 4.0 - Alinata, Reza; Susanti, Emilia; Sari, Winda Atika; Dinillah, Sofyani; Nurfadilah; Sofi, Dian Nirmala (CV. Kurnia Grup, 2024)
The 4.0 Revolution has profoundly changed education, particularly in civic education. This research explores the implementation of digital citizenship in the Civic Education (Civics) curriculum, identifies the challenges, and assesses the relationship between Civics and digital citizenship skills. The study used qualitative methods to explore the integration of information and communication technology in Civics teaching and strategies for developing students' digital skills. The results showed constraints such as limited infrastructure and teachers' professional development needs as the main barriers. However, the integration of digital citizenship has the potential to increase students' understanding and participation in civic practices, both locally and globally. The study recommends adaptive policies and increased investment in teacher training and technological infrastructure, so that civic education can more effectively face the challenges of the digital age. This research underscores the importance of innovative approaches in education to prepare students for a changing society.